CHARACTERISTICS OF GRAM-NEGATIVE NEONATAL SEPSIS AND ASSOCIATED RISK FACTORS AT BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective:To describe the clinical and laboratory characteristics of Gram-negative neonatal infections and to identify risk factors associated with multidrug-resistant (MDR) Gram-negative infections at the Pediatric Center, Bach Mai Hospital, during 2023–2025.Methods:A cross-sectional study combined with a case–control design was conducted among neonates (